Can mobile games protect students against misinformation? A replication study using GoViral! - Nicolaidou, Iolie (My University, 2023)
Misinformation is a pressing societal challenge. A potential solution to this problem is games for social change, which focus on supporting young adults’ digital literacy skills in general and their skills in identifying fake news in a social media context in particular. A game for social change (GoViral!) was designed to fight the spread of misinformation in the context of COVID-19. The game exposes the user to manipulation techniques used in misinformation. There is an ongoing debate about the extent to which misinformation interventions negatively influence people’s assessments of real news. Findings in the literature are ambiguous. Following a study with an English, French, and German-speaking population (Basol et al., 2021), this replication study used an experimental pre-test and post-test design to evaluate the effectiveness of the GoViral! game with a Greek-speaking sample of undergraduate students. Results showed that people who played GoViral! rated misinformation about COVID-19 as significantly more manipulative after gameplay for two out of three fake posts and rated real information as less manipulative for two out of three real posts. Findings are inconclusive, indicating the need for further studies. The study’s findings suggest that players need the most support in identifying the manipulation technique of fake experts in social media. Findings furthermore indicate that interventions aimed at increasing trust in reliable news sources are needed.
Keywords: Misinformation; Digital games; Manipulation techniques; Fake news; Interventions; GoViral!